Idiopathic midline destructive disease--case report and review of the literature. Issue 705 (July 1984) - Robinson, A. C.; Fraser, I.; Bailey, D.; O'Halloran, M. J.
Abstract : A case of idiopathic midline destructive disease (IMDD) in a 39-year-old male is described. Clinical features and diagnosis are discussed. The value of radiotherapy in management is highlighted.